2009
DOI: 10.1088/0004-637x/703/2/2051
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamical Model for the Evolution of a Pulsar Wind Nebula Inside a Nonradiative Supernova Remnant

Abstract: A pulsar wind nebula inside a supernova remnant provides a unique insight into the properties of the central neutron star, the relativistic wind powered by its loss of rotational energy, its progenitor supernova, and the surrounding environment. In this paper, we present a new semi-analytic model for the evolution of such a pulsar wind nebula. This model couples the dynamical and radiative evolution of the pulsar wind nebulae, traces the evolution of the pulsar wind nebulae throughout the lifetime of the super… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
329
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(353 citation statements)
references
References 56 publications
17
329
1
Order By: Relevance
“…We have compared the PWN and SNR sizes with the prediction of the evolutionary model of Gelfand et al (2009) for composite SNRs, and we found excellent agreement. We conclude that the faint diffuse emission around the PWN G54.1+0.3 may indeed be the shell of the associated remnant.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…We have compared the PWN and SNR sizes with the prediction of the evolutionary model of Gelfand et al (2009) for composite SNRs, and we found excellent agreement. We conclude that the faint diffuse emission around the PWN G54.1+0.3 may indeed be the shell of the associated remnant.…”
Section: Discussionmentioning
confidence: 75%
“…If the faint diffuse emission that we have discovered around the PWN G54.1+0.3 is really the associated SNR shell, then we can compare its properties with the PWN-SNR evolutionary model of Gelfand et al (2009). This model couples the dynamical and radiative evolution of the PWN with the dynamical properties of the surrounding non-radiative SNR, and predicts several distinctive evolutionary stages, namely the initial expansion, the reverse shock collision, the re-expansion, and the second compression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This naturally explains the observed high degree of polarization in X-rays, optical, and radio (Moran et al 2013;Bietenholz et al 2004;Weisskopf et al 1978). Multiwavelength observations and modeling show that IC scattering on Cosmic Microwave Background and NIR/IR background starts to dominate PWN spectra in GeV (Acero et al 2013) and completely dominates synchrotron at TeV energies (Atoyan and Aharonian 1996, Volpi et al 2008, Gelfand et al 2009, and Olmi et al 2014; see the Crab and Vela PWN spectra in Fig. 14 for example).…”
Section: Pwn Spectramentioning
confidence: 85%
“…The significant offset of the pulsar from the γ-ray centroid implies either a PWN expansion into an inhomogenous medium, or an asymmetric reverse shock interaction. Either way, models such as Gelfand et al (2009) which compute the PWN compression assuming spherical symmetry cannot be applied.…”
Section: Discussionmentioning
confidence: 99%